PENGEMBANGAN PERUMAHAN SUBSIDI UNTUK PEKERJA INDUSTRI DI KARAWANG - Hubert Winata; Parino Rahardjo (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
Housing has always been a necessity in the lives of modern man. Anyone who was already working needs to own at least some form of housing. Development of a city plays a part in determining the prices of the housing sold whereas in the central and business district houses can be very expensive, the one’s at the outskirt of the town can be cheaper or it can be which will be shown in this research. The government concerned offered developers a project which is known as Subsidized Housing, a house which is cheap with lots of benefits to encourage low income buyers. The industrial sector is known for its High Workforce which implies that a lot of manpower is involved, this creates ample market opportunities. Why don’t we see a lot of subsidized housing? This concerns the fact that not all houses built for this manner yields enough profit to entice developers to actually build them. Thus the research for counting the actual benefit must be done in order to convince developers that there is an acceptable return to be gained when developing Subsidized Housing. The analysis conducted in this research include location analysis, site analysis, legality analysis, comparative object study analysis, preference analysis and financial analysis. The analytical tool used is the analysis of proximity, Discounted Cashflow, Sensitivity Analysis, descriptive and quantitative. The results of this study are the amount of returns obtained by the developer in n years, the length of the return and the percentage of profits. Keywords: building material; developer’s profit; industrial district; subsidized housing ABSTRAKRumah sudah menjadi sesuatu yang wajar dimiliki oleh masyarakat di berbagai kalangan, rumah tidak hanya berperan dalam memberikan perlindungan terhadap cuaca tetapi juga sebagai tempat untuk keluarga berkumpul dan menikmati waktu bersama dengan keluarga maupun orang lain. Tentu tidak semua orang bisa memiliki rumah dengan berbagai alasan, oleh sebab itu pemerintah melakukan intervensi dalam bentuk penyediaan subsidi. Namun mengapa tidak banyak perumahan subsidi dikarenakan pihak pengembang hanya melihat secara singkat seberapa besar pengembalian yang didapat pengembang tingkat pengembalian tersebut yang menentukan apakah pengembang mau atau tidak mengembangkan perumahan subsidi. Dengan pertanyaan tersebut dilakukanlah penelitian pengembangan perumahan perumahan subsidi untuk menunjukkan tingakt keuntungan yang akan didapatkan seorang pengembang beserta lamanya pengembalian modal. Analisis yang dilakukan yakni analisis lokasi, analisis tapak, analisis legalitan, analisis objek studi banding, analisis preferensi dan analisis keuangan. Alat analisis yang digunakan adalah analisis proximitas, Discounted Cashflow, Sensitivity Analysis, deskriptif dan kuatitatif. Hasil dari penelitian ini adalah besarnya pengembalian yang didapatkan pengembang pada tahun n, lama pengembaliannya dan persentase keuntungannya.